How country of origin influences Chinese consumers' evaluation of imported milk?. Issue 1 (22nd September 2020) - Zhang, Yan; Jin, Shaosheng; Zhang, Yu Yvette; Yu, Xiaohua
Abstract : Purpose: The purpose of this study is to decompose the effects of country-of-origin labeling (COOL) into multiple dimensions—macrolevel image, related to the country image, and microlevel image, related to dairy industry/product attributes—and investigate how each dimension affects Chinese consumers' evaluation of imported milk. Design/methodology/approach: This study adopted the Becker–DeGroot–Marschak (BDM) auction mechanism to elicit consumers' willingness to pay (WTP) for milk from different countries (New Zealand, Australia, Germany, France and China). The experiment was conducted with 348 shoppers at supermarkets in three major cities of China (Hangzhou, Wuhan and Shijiazhuang). The study subject was ultrahigh-temperature processing (UHT) milk (200 mL Tetra Pak aseptic brick package). Findings: The results show that Chinese consumers are willing to pay a premium for UHT milk from New Zealand, Australia, Germany and France compared to domestic milk, and the premiums are 59.4, 58.9, 57.9, and 52.9% respectively. Both microlevel and macrolevel images exert a substantial influence on consumers' WTP, and the microlevel image has a greater impact on consumers' evaluation of milk than the macrolevel image. Particularly, the macropolitical, microtechnology/quality and microdesign/package dimensions have a positive influence on WTP for milk. Originality/value: This study contributes to the existing literature in introducing the country-of-origin image (COI) construct with different dimensions to get in-depth knowledge about the country-of-origin (COO) effect in food or agricultural economics.